Comparison of the predictive strength of total white blood cell count within 24 hours on the outcome of traumatic brain injury with cranial computed tomography scan in a resource-limited tertiary health centre in sub-Saharan Africa - Eghosa Morgan; Olufemi Bankole; Okezie Kanu; Omotayo Ojo; Edward Poluyi (Romanian Neurosurgery, 2019)
Background: The enormous disease burden of patients with traumatic brain injury (TBI) remains a huge source of concern to the patient and caregivers. Computed tomography (CCT) scan is a valuable investigative tool in patients with traumatic brain injury which can be used to predict the outcome of TBI. The use of total white blood cell as a predictive parameter in patients with TBI is still at a primordial stage. This study aimed to compare the predictive strength of total WBC count within 24 hours of TBI with cranial computed tomography scan.